Optimizing Supply Chain Management to Reduce Food Waste and Loss in Agriculture - Almusawi Muntather; Obaid Mohammed Kadhim; Hemalatha K. (SHS Web of Conferences, 2025)
Food excess and damage in agriculture contemporary substantial experiments to worldwide food safekeeping and supply organization. In the existing situation, a considerable serving of food does not ever influence clients due to inadequacies in collecting, packing, conveyance, and dispensation. This question not only outcomes in commercial fatalities for farmers but also subsidizes conservational difficulties such as greenhouse gas discharges from decomposing surplus. The problematic declaration highlights that despite progress in cultivated methods, food leftover residues are a determined matter. Several approaches have been working to report this, including enhanced gathering techniques, healthier packing clarifications, well-organized source sequence organization, enhanced processing and packaging, and education and training for farmers. However, the efficiency of these approaches varies, and an incorporated method is essential to accomplish momentous consequences. This investigation recommends augmenting source sequence administration as a crucial approach to diminish food excess and damage in agriculture. By reorganizing logistics and enhancing coordination from farm to market, the proposed system aims to minimize delays and spoilage, ensuring that food products reach regulars in optimum condition. The incorporation of supply chain management with other approaches, such as enhanced loading resolutions and superior handling, is also discovered to deliver a wide-ranging solution. The consequences of this investigation determine that well-organized supply chain management suggestively diminishes food excess, leading to better-quality agricultural efficiency and sustainability. This method offers an accessible and adjustable resolution that can be applied transversely to numerous agricultural contexts, eventually subsidizing worldwide determinations to augment food safekeeping and source proficiency.